THE ROLE OF NATIONALITY IN EDUCATION OF FUTURE MUSIC TEACHERS (American Journal of Interdisciplinary Research and Development, 2025)
The content of this article focuses on the study of experiences in providing future specialists with theoretical and practical knowledge of Uzbek classical music, including maqoms, in educational institutions operating at various stages of the continuing education system. Analytical considerations are made on the specific aspects of musical education.